ACCEPTABLENESS ANALYSIS OF THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY PROGRAMS WITH SOCIAL LICENSE TO OPERATE - Erlina Diamastuti; Fitri Romadhon; Nur Eliza Faizty; Husnunnida Maharani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
This study aims to establish the practice of Corporate Social Responsibility in one of Indonesia's cement companies. CSR practice in some State-Owned Enterprises (BUMN) is mandatory. As an effort of community development, the planned and realized CSR program needs to be evaluated for its acceptability by the community. The indicators to evaluate the effort of community development are to improve a sense of community belonging, including commitment as the ability to solve problems and access to resources. One of the tools that can be used to perform evaluations related to the acceptableness of CSR programs is the Social License to Operate (SLO). The SLO method was implemented through a series of stages: interview, FGD, and questionnaire deployment. Based on these stages, the SLO levels influenced the community's perception of acceptance of implementing CSR programs. SLO assessment showed that one of Indonesia's cement companies had obtained a social license at the approach level. The social license to operate can indicate the success rate of a program received by the community.